Experimental and numerical study of heat transfer and friction factor of plain tube with hybrid nanofluids - A. I., Ramadhan; W. H., Azmi; R., Mamat; Khairiah, Abdul Hamid (Elsevier, 2020)
The use of heat transfer enhancement techniques, can improve the thermal performance of the tubes. In this study, the convective heat transfer from nanoparticles TiO2–SiO2 was dispersed to W/EG in the plain tube, under constant wall heat flux studied numerical and experimental. The type of nanofluid used is the TiO2–SiO2 base fluid EG/water mixture. The volume concentrations used were 1.0, 2.0 and 3.0%. The Reynolds number (Re) used ranges from 2900 to 11,200. The effect of nanofluids on heat transfer coefficients and friction factors is presented in this work. The results show that heat transfer increases with Reynolds number for numerical and experimental in plain tube. Hybrid nanofluids at volume concentration of 3.0% had the highest amount of Nusselt and the highest friction factor was followed by 2.0% and then 1.0%. Experimental and numerical results are compared in terms of Nusselt number average deviation found was 8.8, 8.9 and 7.9% for the volume concentration of 1.0, 2.0, and 3.0% in this study. The friction factor average deviation is 4.1, 3.8 and 3.5% for the volume concentration of 1.0, 2.0, and 3.0%, respectively.